Human radiolabeled mass balance studies supporting the FDA approval of new drugs. Issue 11 (23rd September 2022) - Ramamoorthy, Anuradha; Bende, Girish; Chow, Edwin Chiu Yuen; Dimova, Hristina; Hartman, Neil; Jean, Daphney; Pahwa, Sonia; Ren, Yunzhao; Shukla, Chinmay; Yang, Yuching; Doddapaneni, Suresh; Danielsen, Zhixia Yan
Abstract: Human radiolabeled mass balance studies are an important component of the clinical pharmacology programs supporting the development of new investigational drugs. These studies allow for understanding of the absorption, distribution, metabolism, and excretion of the parent drug and metabolite(s) in the human body. Understanding the drug's disposition as well as metabolite profiling and abundance via mass balance studies can help inform the overall drug development program. A survey of the US Food and Drug Administration (FDA)‐approved new drug applications (NDAs) indicated that about 66% of the drugs had relied on findings from the mass balance studies to help understand the pharmacokinetic characteristics of the drug and to inform the overall drug development program. When such studies were not available in the original NDA, adequate justifications were routinely provided. Of the 104 mass balance studies included in this survey, most of the studies were conducted in healthy volunteers (90%) who were mostly men (>86%). The studies had at least six evaluable participants (66%) and were performed using the final route(s) of administration (98%). Eighty‐five percent of the studies utilized a dose within the pharmacokinetic linearity range with 54% of the studies using a dose the same as the approved dose. Nearly all studies were performed as a single‐dose (97%) study using a fit‐for‐purpose radiolabeled formulation. In this analysis, we summarized the current practices for conducting mass balance studies and highlighted the importance of conducting appropriately designed human radiolabeled mass balance studies and the challenges associated with inadequately designed or untimely studies.